2021
DOI: 10.1167/jov.21.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression is retained in deep networks trained for face identification

Abstract: Facial expressions distort visual cues for identification in two-dimensional images. Face processing systems in the brain must decouple image-based information from multiple sources to operate in the social world. Deep convolutional neural networks (DCNN) trained for face identification retain identity-irrelevant, image-based information (e.g., viewpoint). We asked whether a DCNN trained for identity also retains expression information that generalizes over viewpoint change. DCNN representations were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…1C ). The results indicated that the expression-selective units spontaneously emerged in the VGG-Face pretrained for face identity recognition, which echoed previous findings ( 19 , 20 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1C ). The results indicated that the expression-selective units spontaneously emerged in the VGG-Face pretrained for face identity recognition, which echoed previous findings ( 19 , 20 ).…”
Section: Resultssupporting
confidence: 89%
“…It should be noted that, in our study, the classification accuracies of the expression-selective units in the pretrained VGG-Face were worse than the performance of expression recognition in humans, which was consistent with a recent finding showing that the identity-trained DCNN retained expression information but with expression recognition accuracies far below human performance ( 20 ). The reason for the decreased expression recognition performance deserves future investigation, although it is beyond the scope of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PCA+LDA models suggest that there is enough physical commonality between images to support recognition of familiar faces across their lifespan, suggesting that multiple different representations are not necessary (Mileva et al, 2020). Likewise, DCNNs store diverse images of the same face (e.g., images that vary in viewpoint, lighting, expression) in the same region of face space (Colón et al, 2021;Hill et al, 2019;see O'Toole et al, 2018 for a summary), suggesting that images from multiple decades might reside in close proximity. Nevertheless, any theory derived from computational models should be complemented by behavioural data from humans.…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Two lines of evidence show that DCNNs retain a representation of within-identity variability. First, visualization of the top layer of face space shows that images of an identity are clustered based on viewpoint, lighting, expression, and whether the input was a still image or video (Colón et al, 2021;Hill et al, 2019). Second, classification of image attributes (e.g., expression, viewpoint, whether the input was a still image or video) based on output at the top levels of DCNNs is highly accurate (Colón et al;Parde et al, 2017; see also Dhar et al, 2020 for expressivity as a measure of which image attributes are retained).…”
Section: Practitioner Pointsmentioning
confidence: 99%